2019
DOI: 10.1002/jclp.22865
|View full text |Cite
|
Sign up to set email alerts
|

Coping with discrimination: The insidious effects of gender minority stigma on depression and anxiety in transgender individuals

Abstract: Objectives We examined types of discrimination encountered by transgender and gender diverse (TGD) individuals and the associations with symptoms of depression and anxiety, as well as the mediating and moderating effects of coping responses. Method This online study included 695 TGD individuals ages 16 years and over (M = 25.52; standard deviation = 9.68). Results Most participants (76.1%) reported discrimination over the past year. Greater exposure to discrimination was associated with more symptoms of depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 66 publications
3
61
0
2
Order By: Relevance
“…Findings established that LGBTQ+ young people perceive themselves to be using multiple strategies to self-manage their mental health and perceive there to be a number of barriers and facilitators to this process. These findings support further exploration into the development of or provision of research-informed support to an intervention or policy to support self-management, particularly that which can be tailored for specific groups (e.g., gender diverse individuals), as some groups might find particular ways of self-managing their mental health more helpful than others [32]. A key area of future investigation should be into social and LGBTQ+ youth group or community support as key facilitators to the self-management of mental health, as these were highlighted by participants in the current study and have implications for policy and intervention development.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Findings established that LGBTQ+ young people perceive themselves to be using multiple strategies to self-manage their mental health and perceive there to be a number of barriers and facilitators to this process. These findings support further exploration into the development of or provision of research-informed support to an intervention or policy to support self-management, particularly that which can be tailored for specific groups (e.g., gender diverse individuals), as some groups might find particular ways of self-managing their mental health more helpful than others [32]. A key area of future investigation should be into social and LGBTQ+ youth group or community support as key facilitators to the self-management of mental health, as these were highlighted by participants in the current study and have implications for policy and intervention development.…”
Section: Discussionsupporting
confidence: 58%
“…The negative impact of the lockdown on LGBTQ+ young people’s mental health was echoed in research by Kneale and Becares [ 31 ], who found high levels of both stress and depressive symptoms amongst LGBTQ+ people during the lockdown, particularly in the case of younger and transgender respondents, as they were more likely than others in the LGBTQ+ community to have experienced some form of discrimination during the pandemic. Experiences of discrimination such as these have been associated with greater symptoms of emotional difficulties like anxiety and depression amongst transgender people [ 32 ]. The findings from the current study did not suggest that participants had experienced additional discrimination during the lockdown, but instead that the barriers to self-management resulting from the pandemic were partly perceived to be due to not being able to access vital services, attend LGBTQ+ youth groups, socialise as often with friends or attend extracurricular activities due to closures.…”
Section: Discussionmentioning
confidence: 99%
“…Some say we have even reached a “trans tipping point” (Steinmetz, 2014) in socio‐cultural advances. Nonetheless, TGD people face significant political backlash, further entrenchment in a rigid gender binary, and high levels of violence, stigma, and discrimination targeting in particular trans women of color (Grant, Motter, & Tanis, 2011; Puckett, Maroney, Wadsworth, Mustanski, & Newcomb, 2019; White Hughto, Reisner, & Pachankis, 2015). These adversities in turn contribute to health disparities among TGD people as compared to the general population (Downing & Przedworski, 2018; Reisner et al, 2016; Su et al, 2016; Winter et al, 2016).…”
Section: Toward a Human Biology Of Gender/sex And Sexual Diversitymentioning
confidence: 99%
“…Die zuvor beschriebenen Diskriminierungserfahrungen gehen oft mit Depressions-und Angstzuständen einher [15]. TM-Patienten, die sich im Anfangsstadium ihrer Geschlechtsanpassung befinden, wenden oftmals vermeidungsorientierte Copingstrategien an, was mit Depression und Angstzuständen in Zusammenhang steht [1].…”
Section: Soziale Einbindung Als Zentrale Bewältigungsressourceunclassified